Introduction to MXenes: synthesis and characteristics. (December 2019) - Salim, O.; Mahmoud, K.A.; Pant, K.K.; Joshi, R.K.
Abstract: MXenes exhibit a special combination of high hydrophilicity and metallic conductivity rendered by the existence of surface terminations (–O, –F, and –OH) and transition metal carbide/nitride. Besides, MXenes combine other unique characteristics, such as high strength and stiffness. We understand that MXenes are materials with huge potential for applications and significant addition to the two-dimensional materials family. Therefore, a review article briefly covering all areas related to MXene for a broader audience is in demand. It demonstrates how MXenes have evolved and advanced since its discovery. Graphical abstract: Image 1 Highlights: MXenes are new materials in two-dimensional materials family with huge potential for applications. MXenes have potential to be used in the areas of hydrogen storage, supercapacitors, batteries, and desalination. This article presents how MXenes have evolved and advanced since discovery.